Macroeconomic Effects of EU Transfers in New Member States. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Large inflows from the European Union to the New Member States are likely to significantlyimpact macroeconomic outcomes. In this paper, we use the IMF's Global Integrated Monetaryand Fiscal model (GIMF) to analyze the impact of the transfers and show the conditionsunder which they would help speed up convergence. We find that the EU funds need to bedirected predominantly to investment rather than to income support and that to bestaccompany the EU fund inflows, the policy-mix would need to combine counter-cyclicalpolicy with a strong commitment to the existing monetary regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet